2017
DOI: 10.1186/s40168-017-0365-4
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and genetic factors shape the microbiome of a seabird species (Oceanodroma leucorhoa) more than environmental and social factors

Abstract: BackgroundThe microbiome provides multiple benefits to animal hosts that can profoundly impact health and behavior. Microbiomes are well-characterized in humans and other animals in controlled settings, yet assessments of wild bird microbial communities remain vastly understudied. This is particularly true for pelagic seabirds with unique life histories that differ from terrestrial bird species. This study was designed to examine how morphological, genetic, environmental, and social factors affect the microbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
85
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(91 citation statements)
references
References 101 publications
5
85
1
Order By: Relevance
“…The heritability of the avian microbiome, and especially in these species, is unknown but there are several pieces of evidence to support that the microbiome may be at least partially heritable. First, there is a negative correlation between genetic distance and microbiome similarity in multiple bird species (e.g., Banks, Cary, & Hogg, ; Pearce, Hoover, Jennings, Nevitt, & Docherty, ), indicating that host genetics exert some control on the microbiome. Second, the members of the microbiome are not a random sample of the environment and this selection, whether direct or indirect, is a property that may be vertically transmitted.…”
Section: Discussionmentioning
confidence: 99%
“…The heritability of the avian microbiome, and especially in these species, is unknown but there are several pieces of evidence to support that the microbiome may be at least partially heritable. First, there is a negative correlation between genetic distance and microbiome similarity in multiple bird species (e.g., Banks, Cary, & Hogg, ; Pearce, Hoover, Jennings, Nevitt, & Docherty, ), indicating that host genetics exert some control on the microbiome. Second, the members of the microbiome are not a random sample of the environment and this selection, whether direct or indirect, is a property that may be vertically transmitted.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the associations between MHC and microbiota were detected in neck and preen feathers, but not in dorsal and ventral feathers. Similarly, in the Leach's storm petrel ( Oceanodroma leucorhoa ), a species phylogenetically closely related to the blue petrel, MHC is associated with microbiota of the preen gland area, but not with that of the brood patch (Pearce et al, ). Compared to ventral and dorsal feathers, neck feathers are highly coated with preen secretions (Supporting information Figure ), which might suggest that the covariation between MHC and neck feather microbiota arises from a proximal mechanism originating in preen secretions.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies in mice, rats, fish and humans have found covariation between MHC variation and the composition of bacterial communities in the gut (Bolnick et al, ; Kubinak et al, ; Lanyon et al, ; Lin et al, ; Toivanen, Vaahtovuo, & Eerola, ), but only a single study has so far focused on plumage microbiota (Pearce, Hoover, Jennings, Nevitt, & Docherty, ). To test the potential role of plumage microbiota in the production of MHC–odour signals, we therefore set out to test whether (a) within‐individual MHC diversity and (b) the degree of MHC dissimilarity between individuals correlated with plumage microbiota assemblage in blue petrels ( Halobaena caerulea ).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, genetic variation may encode variable responses in the host immune system to microbes in the environment. In other species, polymorphism in immunity-related genes has been found to affect microbiome composition (Bolnick et al, 2014;Kubinak et al, 2015;Pearce et al, 2017) and responses to pathogenic bacteria (Lazzaro, Sceurman, & Clark, 2004). In addition, genotype-specific immune response, and varying gene expression patterns in response to a potentially pathogenic bacteria, have been observed in the coral Acropora millepora (Wright et al, 2017).…”
Section: Host Genotypementioning
confidence: 99%
“…However, given the strength of host identity in structuring the microbiome, genetic variation within the species may also be significant. Indeed, host genotype influences microbiome composition in several systems, including plants (Wagner et al, 2016), fish (Uren Webster, Consuegra, Hitchings, & Garcia de Leaniz, 2018), amphibians (Griffiths et al, 2018), birds (Pearce, Hoover, Jennings, Nevitt, & Docherty, 2017) and mammals (Benson et al, 2010;Goodrich et al, 2014). However, host genotype and microbial variation have not yet been linked in sponges.…”
Section: Introductionmentioning
confidence: 99%